PENGARUH STRATEGI DIFERENSIASI PRODUK, CITRA MEREK, DAN MEDIA IKLAN TERHADAP KEPUTUSAN PEMBELIAN MINYAK GORENG DALAM KEMASAN MEREK SANIA ROYALE PADA MASYARAKAT PERUMAHAN TANGERANG, TANGERANG SELATAN DAN BOGOR - Rahayu Lestari; Beureukat Beureukat (Universitas Mercu Buana, 2015)
Respondents were used in this study were housewives who buy and use as well as to comment thatcooking with cooking oil Sania Royale will give fragrance to the dish and providea more delicious flavorcompared to other brands. PT. Multimas Nabati Asahan been producing and selling previously cooking oil in packing Sania. Based on the phenomenon exists within the housing community Tangerang, Tangerang andBogor South, the authors conducted a study to determine how much influence product differentiation,brand image, media advertising on consumer buying decisions in the cooking oil brand packaging SaniaRoyale. The method chosen should be appropriate to analyze the pattern of research and variables that willbe investigated. The Structural Equation Modeling (SEM) used to hypothesis testing. The analysis showedthat the advantages of the service attribute sand influence there feree's satisfaction and word of mouthmarketing performance and satisfaction of product differentiation does not have a real and positiveinfluence on purchasing decisions. While the brand image and the Media Advertising has a real and positiveinfluence on purchasing decisions.